Strength Analysis of the Truck Wheel Rim Robot Gripper - Tiknis, Mindaugas; Sabaliauskas, Arturas (Jaunųjų mokslininkų darbai, 2021)
This paper presents a study of the strength of the truck rim robot gripper structure using the finite element analysis system Solidworks Simulation. The developed CAD model of the gripper was adapted to the research by Solidworks Simulation system, which was used to evaluate the strength and stiffness of the structure. Construction optimization was performed, the obtained results were compared.
Keywords: gripper; strength; FEM